In vitro and in silico β-lactamase inhibitory properties and phytochemical profile of Ocimum basilicum cultivated in central delta of Egypt - Nagwa A. Shoeib; Lamiaa A. Al-Madboly; Amany E. Ragab (Taylor & Francis Group, 2022)
Context Some studies reported the chemical content and antimicrobial properties of Ocimum basilicum L. (Lamiaceae), relevant to the ecological variations in some areas of Egypt and other countries, yet no research was conducted on the plant cultivated in the central delta region of Egypt. Also, no previous data reported on inhibition of β-lactamases by O. basilicum.Objective To assess β-lactamases inhibition by O. basilicum extracts and the individual constituents.Materials and methods Dried aerial parts of O. basilicum were extracted by hydrodistillation for preparation of essential oil and by methanol for non-volatile constituents. Essential oil content and the methanol extract were analysed by GC-MS and UPLC-PDA-MS/MS, respectively. Methyl cinnamate was isolated and analysed by NMR. Broth microdilution method was used to investigate the antimicrobial against resistant clinical isolates of Escherichia coli identified by double disc synergy, combination disc tests and PCR. The most active oil content was further tested with a nitrocefin kit for β-lactamase inhibition and investigated by docking.Results O. basilicum was found to contain methyl cinnamate as the major content of the essential oil. More interestingly, methyl cinnamate inhibited ESBL β-lactamases of the type CTX-M. The in vitro IC50 using nitrocefin kit was 11.6 µg/mL vs. 8.1 µg/mL for clavulanic acid as a standard β-lactamase inhibitor.Discussion and conclusions This is the first study to report the inhibitory activity of O. basilicum oil and methyl cinnamate against β-lactamase-producing bacteria. The results indicate that methyl cinnamate could be a potential alternative for β-lactamase inhibition.